Thermoelastic damping analysis in micro and nanomechanical systems under generalized thermoelasticity and non-classical continuum theories - Kumar, Harendra (IIT(BHU) Varanasi, 2022)
Abstract is available in attachment.
This thesis is uploaded by IIT BHU
Keywords: Thermoelastic; damping; analysis; non-classical